Community-Partnered Evaluation of the Aging Mastery Program in Los Angeles Area Senior Centers. (February 2020) - Guerrero, Lourdes R.; Menkin, Josephine A.; Carrillo, Carmen A.; Reyes, Carmen E.; Trejo, Laura; Banks, Cynthia; Sarkisian, Catherine A.
Background. The National Council on Aging's Aging Mastery Program (AMP) aims to help older adults implement health behavior and lifestyle changes to promote healthy aging and social engagement. The purpose of the present community-partnered evaluation was to test the effectiveness of AMP implementation in Los Angeles County to improve participants' quality of life, global physical and mental health, and patient activation. Method. A modified randomized wait-list controlled trial design was used to examine experimental, quasi-experimental, and dose-response evidence in five senior centers. Participants completed questionnaires at baseline and after the 10-week intervention, self-reporting their overall quality of life, physical health, mental health, and patient activation. Results. Experimental, intention-to-treat analyses found AMP assignment did not affect any measured outcomes ( n = 71). Quasi-experimental, "as treated" analyses ( n = 106) controlling for study site and sociodemographic characteristics indicated that participants who attended AMP reported more positive changes in global mental health than the control group. Attending AMP was not associated with changes in quality of life, physical health, or patient activation. Dose-response analyses among AMP participants who attended at least one class ( n = 75) found that attending more classes was not significantly associated with greater improvements in mental health. Conclusions. Experimental, intention-to-treat analyses did not support effectiveness of AMP on quality of life, physical or mental health, or patient activation; quasi-experimental analyses found attending AMP was associated with improvements in mental health. Recruitment challenges and participants' nonadherence with condition assignment decreased our ability to detect effects.https://clinicaltrials.gov/ct2/show/NCT03342729?term=Aging+Mastery+Program&rank=1 .